PENGARUH PERBEDAAN LOKASI MENCARI MAKAN TERHADAP KERAGAMAN MANGSA TIGA JENIS KUNTUL DI CAGAR ALAM PULAU DUA SERANG: Casmerodius albus, Egretta garzetta, Bubulcus ibis - Elfidasari, Dewi (Makara Journal of Science, 2023)
Prey diversity influenced by the different or foraging areas for three species herons in Cagar Alam Pulau Dua Serang. This research is to know the influenced of foraging areas to prey diversity for three species herons in Cagar Alam Pulau Dua Serang, Banten Province. This research have been done at feeding area for the herons around Cagar Alam Pulau Dua. The data were from film shooting use Focal Observation Methods, while the film shooting analyze use scan sampling methods. It’s explain that Casmerodius albus and Egretta garzetta have preferency to select the mudflat and fisheries around CAPD as foranging location because they preferency to select fish as they main prey. Bubulcus ibis who select to using rice-field and grassland as a foraging location have preferency to select insects as a main prey. The selection of foraging location for three species herons are depend on the spesific kind and size of preys for them. The preferency for Casmerodius albus to feedinginest is mudflat with the mayority prey are big fish, with the size of more than 15 cm. Egretta garzetta have preferency to select fisheries because they main prey are fish with size of about 3-5 cm. Bubulcus ibis is prefer to feeding in grassland because they eat the insect with the preferences prey size smaller than 3 cm.